Early assessments in the Swedish preschool class: Coexisting logics - Ackesjö, Helena (CEPRA-striben, 2021)
In this paper, teachers’ work with the newly introduced assessment of six-year-old children in Sweden is illustrated using the neoinstitutional theory. The results show how teachers are guided by coexisting mix of logics, which are based on different values and lead to different assessment practices. The results show that more assessment implies less teaching, and the policy reform vision, to better support children in continuing education, is at risk of being lost when transformed to pedagogical practice. The formative focus on the assessments is reduced to a technical practice with focus on delivering results. Thus, the neoliberal focus and performativity is prominent.